Patient Satisfaction and Sanitation Standards: A Study of Hospital Environments in Kathmandu - Adhikari, Surakshya; Pandey, Gita; Raikhola, Pushkar Singh (NPRC Journal of Multidisciplinary Research, 2024)
Background: Hospital environments and sanitation play a critical role in influencing patient satisfaction and overall healthcare outcomes. Despite its significance, this aspect often remains underexplored, particularly in the context of diverse patient demographics in urban healthcare settings. Objective: The study aimed to evaluate patient satisfaction with hospital environments and sanitation practices in Kathmandu, focusing on demographic influences and patient experiences. Methods: A deductive and descriptive research design was employed, involving 109 patients from various hospitals in Kathmandu. Participants, aged 15 years and above, were selected through a convenient sampling method. Data were collected using a structured questionnaire covering demographic factors, hospital admission methods, and patient perceptions of sanitation and treatment outcomes. Descriptive statistics, including frequencies and percentages, were used to analyze the data. Results: The majority of participants were aged 20-25 years (38.5%), with a near-equal gender distribution (52.3% male and 47.7% female). A significant portion were single (67%) and held graduate-level education (39.4%). Nearly half of the respondents were students (49.5%), and 45.9% reported monthly incomes between NPR 5,000-10,000. Most participants accessed hospitals via the Outpatient Department (73.4%) and had been admitted 1-2 times (56%). Short hospital stays (2 days) were most common (47.7%). An overwhelming majority (98.2%) reported health improvements after treatment, highlighting patient satisfaction. Conclusion: Patient satisfaction with hospital environments and sanitation in Kathmandu is influenced by demographic factors such as age, education, and income. Findings underscore the need for tailored strategies to improve hospital sanitation and enhance patient experiences, particularly for young adults and economically disadvantaged groups.